Case report: appendicitis induced Staphylococcus aureus and Klebsiella pneumoniae bacteremia in a young healthy male - Deodatus, Jan Arne Arne (Int J Emerg Med, 2021)
BACKGROUND: Appendicitis is one of the most frequently encountered conditions at the emergency department. Distinction is made between complicated and uncomplicated appendicitis. Complicated appendicitis may cause serious intra-abdominal infection, bacteremia, or sepsis. Emergency health providers should be highly alert to any early signs indicating such complications. CASE PRESENTATION: We present the case of a healthy young male with a gangrenous appendicitis, who received antibiotics and underwent appendectomy. Blood cultures showed unequivocal Staphylococcus aureus and concomitant Klebsiella pneumoniae bacteremia requiring prolonged antibiotic treatment and further diagnostic evaluation. CONCLUSIONS: Although rare, appendicitis can cause Staphylococcus aureus and Klebsiella pneumoniae bacteremia with extensive implications for workup and antibiotic management. Our case stresses the importance of obtaining cultures in patients with suspicion of bacteremia given its consequences for clinical management.